Major Stressors and Coping Strategies of Internal Migrant Workers During the COVID-19 Pandemic: A Qualitative Exploration - Srivastava, Akanksha; Arya, Yogesh Kumar; Joshi, Shobhna; Singh, Tushar; Kaur, Harleen; Chauhan, Himanshu; Das, Abhinav (Frontiers in Psychology, 2021)
Covid-19 forced lockdown in India, lead to the loss of job, crisis of food, and other financial catastrophes that lead to the exodus migration of internal migrant operating in the private sector workers back to their homes. Unavailability of transport facilities led to an inflicted need to walk back to homes barefooted without lack of any other crucial resources on the way. The woeful state of internal migrant workers walking back, with all their stuff on their back, holding their child, was trending on social media worldwide. Their problem continued even after reaching home, including misbehaviour of villagers, indifferent mannerism of family members towards them, inability to fulfil family responsibility, and financial crisis, which lead to stress, fear, and trauma for internal migrant workers. The present paper aimed to assess the idiosyncratic stressors of internal migrant workers throughout the pandemic era and their responses towards those problems, which helped them cope with it. In-depth semi-structured telephonic interviews were conducted with 25 internal migrant workers who were working in different cities in India before lockdown. The analyses revealed that multiple stressors include financial crisis, unavailability of food, inability to continue education, inability to pay house rent, lack of support from neighbours and family, and other psychological stressors that affected them. However, they also tried multiple strategies to deal with the problems, including a cognitive appraisal of the problem and making oneself psychologically competent to deal with the situation. Social support of family and friends played a vital role in enhancing hardiness and increasing the level of happiness at scarce times. At the same time, some of them could not deal with stressors and opted for psychiatric help to manage the physical symptoms of stress.